Libertas and Res Publica in the Roman Republic : Ideas of Freedom and Roman Politics - Balmaceda, Catalina (Impact of Empire, 2021)
Libertas and Res Publica in the Roman Republic offers some essential ideas for an understanding of Roman politics during the Republican period by analysing two key concepts: libertas (liberty) and res publica (public matter, republic). Exploring these concepts through a variety of different aspects - legal, religious, literary, political, and cultural - this book aims to explain the profound relationship between the two. Through the examination of a rich array of sources ranging from classical authors to coins, from legal texts to works of art, Balmaceda and her co-authors propose new readings that elucidate the complex meanings and inter-related functions of libertas and res publica , in a thought-provoking, deep, but very readable study of Roman political culture and identity.